Developing an online reproductive health module on sexually transmitted infections for Indonesian adolescents: a qualitative mixed methods study - Nilasari, Hanny; Indriatmi, Wresti; Gunardi, Hartono; Kayika, I Putu Gede; Kekalih, Aria; Siregar, Kemal Nazaruddin; Kurniawan, Kristian; Lesmana, Elvira; Haswinzky, Rose Amalia (Medical Journal of Indonesia, 2024)
BACKGROUND A notable rise in sexually transmitted infection (STI) cases among youth correlates with a lack of reproductive health awareness, affecting nearly 80% of Indonesian adolescents. Additionally, sociocultural taboo acts as a challenge to reproductive health implementation in Indonesia. Therefore, this study aimed to develop an online reproductive health module focused on STIs for Indonesian adolescents. METHODS This research was a mixed methods approach, integrating quantitative study using univariate analysis (survey and questionnaire) and qualitative study using the Delphi method (open discussion and focus group discussion). The study was conducted between March 2 and July 28, 2022. We began by conceptualizing a literature-based module, an online survey, and virtual discussions involving students, teachers, and parents. Then, we consulted with clinical psychologists and dermatovenereologists. Additionally, students completed an assessment to establish a baseline of their knowledge, attitudes, and behaviors (KAB) regarding reproductive health and STIs. RESULTS Of 327 high school students across Jakarta, analysis of the 129 completed KAB surveys showed that only 56.6% and 65.1% attained acceptable scores (>65) for knowledge and behavior, respectively, with 24.8% being at risk for STIs. Key recommendations included incorporating multimedia elements, ensuring clarity and simplicity in language, adopting non-judgmental tone, providing comprehensive explanations of STIs and their long-term impact, and supporting learning with face-to-face sessions and ongoing access to concise, cost-effective educational resources. CONCLUSIONS Adolescents need a comprehensive, interactive, instructive, accessible, non-discriminatory reproductive module that strengthens the self-concept that upholds Indonesian values and norms.